Optic nerve head and retinal blood flow regulation during isometric exercise as assessed with laser speckle flowgraphy. - Katarzyna J Witkowska; Ahmed M Bata; Giacomo Calzetti; Nikolaus Luft; Klemens Fondi; Piotr A Wozniak; Doreen Schmidl; Matthias Bolz; Alina Popa-Cherecheanu; René M Werkmeister; Gerhard Garhöfer; Leopold Schmetterer (PLoS ONE)
The aim of the present study was to investigate regulation of blood flow (BF) in the optic nerve head (ONH) and a peripapillary region (PPR) during an isometric exercise-induced increase in ocular perfusion pressure (OPP) using laser speckle flowgraphy (LSFG) in healthy subjects. For this purpose, a total of 27 subjects was included in this study. Mean blur rate in tissue (MT) was measured in the ONH and in a PPR as well as relative flow volume (RFV) in retinal arteries (ART) and veins (VEIN) using LSFG. All participants performed isometric exercise for 6 minutes during which MT and mean arterial pressure were measured every minute. From these data OPP and pressure/flow curves were calculated. Isometric exercise increased OPP, MTONH and MTPRR. The relative increase in OPP (78.5 ± 19.8%) was more pronounced than the increase in BF parameters (MTONH: 18.1 ± 7.7%, MTPRR: 21.1 ± 8.3%, RFVART: 16.5 ±12.0%, RFVVEIN: 17.7 ± 12.4%) indicating for an autoregulatory response of the vasculature. The pressure/flow curves show that MTONH, MTPRR, RFVART, RFVVEIN started to increase at OPP levels of 51.2 ± 2.0%, 58.1 ± 2.4%, 45.6 ± 1.9% and 45.6 ± 1.9% above baseline. These data indicate that ONHBF starts to increase at levels of approx. 50% increase in OPP: This is slightly lower than the values we previously reported from LDF data. Signals from the PPR may have input from both, the retina and the choroid, but the relative contribution is unknown. In addition, retinal BF appears to increase at slightly lower OPP values of approximately 45%. LSFG may be used to study ONH autoregulation in diseases such as glaucoma. Trial registration ClinicalTrials.gov NCT02102880.